PANORAMIC DENTAL X-RAY AND PERIODONTITIS: A RETROSPECTIVE ANALYSIS OF RADIOGRAPHIC-BASED PERIODONTAL BONE LOSS (R-PBL) - Cristian Funieru; Oana Amza; Dana Bodnar; Oana Slușanschi; Adrian Țandără; Daniela Vrînceanu (Romanian Journal of Oral Rehabilitation)
Aim of the study: The main goal of this study is to analyze a group of panoramic X-rays using the resorption periodontal bone loss (R-BL) in order to diagnose periodontitis. Materials and methods: 65 of panoramic X-rays were included in this analysis. The measurements of the root length and total bone height were done on mesial and distal surfaces, using a special software processor specifically designed and used for radiographic measurements. The R-PBL scores were analyzed for every surface (mesial and distal), on the entire sample and on gender subgroups. Results: The mean R-PBL score for the entire sample was 14.32%. The highest scores were observed around first molars and central incisors. It seems like men tend to have/ have higher values of R-PBL. Conclusions: R-PBL was a good instrument to analyze panoramic X-rays related to diagnosis of the periodontitis.